Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content: 1. Designing pedestrian roads on campus: The female students’ colleges at the University of Hail as a model Dr. Eman Abdulaziz Al-Saif 2. The role of Social media in enhancing intellectual security in Saudi society -Twitter as a model- An applied and analytical study for the Global Center for Combating Extremist Ideology (Etidal) Mr. Mohammad Ibrahim Alsowailem 3. Nabataean trade deities Mrs. Rawan Faisal Alrehaili, Prof. Abdullah Abdulrahman Alabdaljabbar 4. The role of media education in enhancing recipient awareness A survey study on a sample of students from the Department of Media and Communication at King Khalid University The period from January 2022 AD - January 2023 AD Dr. Hagir Abdalla Gadalla Ali 5. Analytical study of sustainability in ready-made clothes Mrs. Manahil Mansour Omar Al-Qurashi, Co-Prof. Naglaa Jaber Dhifallah Al-Thabiti 6. The impact of natural and human factors on the spread of deaths in Yemen during the era of The Rasulid state (626-858 AH) Dr. Samira Saud Al-Mohammadi 7. Studying the personal and social variables associated with the empowerment of Saudi women – A field study on a sample of women in the city of Al-Ahsa, Kingdom of Saudi Arabia – Mrs. Luluh Abdulhamid Alnaim